Reduced Insulin Clearance and Insulin-Degrading Enzyme Activity Contribute to Hyperinsulinemia in African Americans - Fosam, Andin (J Clin Endocrinol Metab, 2020)
BACKGROUND: African Americans (AAs) are at a higher risk for developing type 2 diabetes compared with non-Hispanic whites (NHWs). The causal role of β-cell glucose sensitivity (β-GS) and insulin clearance in hyperinsulinemia in AA adults is unclear. OBJECTIVE: Using a cross-sectional study design, we compared β-cell function and insulin clearance in nondiabetic AAs (n = 36) and NHWs (n = 47) after a mixed meal test (MMT). METHODS: Insulin secretion rate, glucose sensitivity, rate sensitivity, and insulin sensitivity during MMT were derived from a mathematical model. Levels of insulin-degrading enzyme (IDE) and carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM1), key players in insulin clearance, were measured (by enzyme-linked immunosorbent assay) in hepatic cytosolic fractions from age-, sex-, and body mass index–matched AA and NHW cadaveric donors (n = 10). RESULTS: Fasting and mean postprandial plasma glucose levels were similar in both ethnic groups. AAs had significantly higher fasting and mean postprandial plasma insulin levels. However, fasting ISR, total insulin output, and insulin sensitivity during MMT were not different between the groups. β-GS and rate sensitivity were higher in AAs. Fasting and meal plasma insulin clearance were lower in AAs. Hepatic levels of IDE and CEACAM-1 were similar in AAs and NHWs. Hepatic IDE activity was significantly lower in AAs. CONCLUSIONS: In this study, lower insulin clearance contributes to higher plasma insulin levels in AAs. Reduced insulin clearance may be explained by lower IDE activity levels in AAs. Further confirmatory studies are needed to investigate diminished insulin clearance in AAs as a result of lower IDE activity levels.